Outcomes in Patients Receiving Treatment for Pulmonary Arterial Hypertension Associated With Repaired Congenital Heart Disease - Krasuski, Richard A; Tobore, Tobore; Studer, Sean; Jansa, Pavel; Sitbon, Olivier; Hoeper, Marius M; Channick, Richard; Gaine, Sean; Lang, Irene; Chin, Kelly; Pulido, Tomas; Mehta, Sanjay; et al. (JACC. Advances, 2025)
BACKGROUND: Pulmonary arterial hypertension (PAH) is a common complication among patients with congenital heart disease (CHD). Despite advances in PAH treatment, evidence for the benefits of PAH therapies in CHD-PAH is limited. OBJECTIVES: This analysis aimed to evaluate outcomes in patients with repaired PAH-CHD receiving an approved PAH drug. METHODS: This was a pooled analysis including CHD-PAH patients whose CHD was repaired ≥1 year prior from 3 randomized, placebo-controlled, event-driven studies: GRIPHON (NCT01106014), SERAPHIN (NCT00660179), and COMPASS-2 (NCT00303459). The primary endpoint was time to first confirmed morbidity/mortality (M/M) event. HRs with 95% CIs were determined with random effects models. RESULTS: The analysis included 1,982 patients with PAH, 177 (8.9%) with CHD-PAH. In the overall PAH cohort, the mean age was 48 and 49 years in treatment and placebo groups; 80% and 77% were female. In the CHD-PAH cohort, the mean age was 41 and 39 years; 70% and 66% were female. Overall, ≥98% in each group were World Health Organization functional class II and III at baseline. There was a significant reduction in risk of M/M events vs placebo in the overall PAH and CHD-PAH cohorts: 37% reduction in the overall PAH cohort (HR: 0.63; 95% CI: 0.52-0.77) and 50% reduction in the CHD-PAH population (HR: 0.50; 95% CI: 0.26-0.94). CONCLUSIONS: Treatment with approved PAH drugs provided a similar reduction in M/M risk in patients with repaired CHD-PAH when compared with the overall PAH population. This pooled analysis provides important evidence to guide medical management in this patient population.
Keywords: COMPASS-2; GRIPHON; pooled analysis; congenital heart disease; pulmonary arterial hypertension; SERAPHIN